2015
DOI: 10.18632/oncotarget.3951
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human alpha fetoprotein synergistically potentiates the anti-cancer effects of 1′-S-1′-acetoxychavicol acetate when used as a complex against human tumours harbouring AFP-receptors

Abstract: PurposePrevious in vitro and in vivo studies have reported that 1′-S-1′-acetoxychavicol acetate (ACA) isolated from rhizomes of the Malaysian ethno-medicinal plant Alpinia conchigera Griff (Zingiberaceae) induces apoptosis-mediated cell death in tumour cells via dysregulation of the NF-κB pathway. However there were some clinical development drawbacks such as poor in vivo solubility, depreciation of biological activity upon exposure to an aqueous environment and non-specific targeting of tumour cells. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
2
23
1
Order By: Relevance
“…For example, ACA reduced tumor volume and side effects in vivo when used in combination with alpha-fetoprotein (AFP). 52 …”
Section: Discussionmentioning
confidence: 99%
“…For example, ACA reduced tumor volume and side effects in vivo when used in combination with alpha-fetoprotein (AFP). 52 …”
Section: Discussionmentioning
confidence: 99%
“…1’S-1-acetoxychavicol acetate (ACA) is a phenylpropanoid isolated from rhizomes of Alpinia conchigera Griff. Our group had previously reported the anti-cancer effects of ACA in breast (MCF-7), oral (HSC-2 and HSC-4), liver (HepG2), cervical (CaSki), lung cancer (A549) and prostate carcinoma (PC-3) via inducing apoptosis with minimal cytotoxic effect on normal human mammary cells (HMEC) and no physiological alteration in in vivo model [ 12 14 ]. It was reported that ACA targets NF-κB signalling pathway to alter the pro-inflammatory microenvironment environment both in vitro and in vivo [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our group had previously reported the anti-cancer effects of ACA in breast (MCF-7), oral (HSC-2 and HSC-4), liver (HepG2), cervical (CaSki), lung cancer (A549) and prostate carcinoma (PC-3) via inducing apoptosis with minimal cytotoxic effect on normal human mammary cells (HMEC) and no physiological alteration in in vivo model [ 12 14 ]. It was reported that ACA targets NF-κB signalling pathway to alter the pro-inflammatory microenvironment environment both in vitro and in vivo [ 12 , 14 ]. Despite numerous reports on its direct interaction on signalling pathway, ACA can modulate epigenetic machinery in cancer by altering miRNA expression that eventually has an impact in the gene expression [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Receptor-positive embryo and cancer cells have definite benefits of targeted nutrient delivery ( Figure 1). That is why AFP loaded with the different toxins was used for the targeted chemotherapy [6,7]. The AFP receptor detection on the major immune suppressive cells -MDSC -was very promising [8,9].…”
Section: Introductionmentioning
confidence: 99%